A low-shrinkage alcohol-resistant disinfectant PC / PBT alloy material and preparation method thereof
By adding octphenylcyclotetrasiloxane and isopropyl titanate to the PC/PBT alloy material, the problem of cracking of existing materials when using alcohol disinfectants is solved, and the shrinkage rate of the material is reduced, achieving the dual effects of tolerance to alcohol disinfectants and mold application.
Patent Information
- Application Number
- CN202311830136.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-28
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2043-12-28
AI Technical Summary
Existing PC or PC/ABS materials are prone to cracking problems when using alcohol disinfectants, and highly crystalline PBT materials increase the shrinkage rate of the material, resulting in the non-universal mold.
The PC/PBT alloy material is used to reduce the shrinkage and erosion of alcohol disinfectants by adding octphenylcyclotetrasiloxane to the PC/PBT alloy as the alcohol resistance agent and isopropyl titanate as the shrinkage adjustment agent.
It realizes that materials suitable for PC or PC/ABS low-shrinkage molds without changing the mold, reducing the shrinkage rate of the material and the erosion of alcohol disinfectants, and improving the alcohol-resistant disinfectant performance of the material.
Smart Images

Figure SMS_1 
Figure SMS_3 
Figure SMS_4
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer materials and relates to a low-shrinkage alcohol-resistant disinfectant PC / PBT alloy material and a preparation method thereof. Background Art
[0002] Polycarbonate is a thermoplastic engineering plastic with the characteristics of low water absorption, light weight, high transparency, good heat resistance, good cold resistance, flame retardancy and good insulation. It is widely used in the field of medical devices and equipment due to its excellent impact resistance, creep resistance and dimensional stability. The high virus and bacteria environment of medical equipment inevitably requires frequent disinfection of the medical equipment shell. At present, the most widely used disinfectants in the medical system are alcohol disinfectants, such as ethanol and isopropyl alcohol. However, due to the poor chemical resistance of PC or PC / ABS materials, when using alcohol disinfectants to disinfect the medical equipment shell, the medical equipment shell is very prone to cracking.
[0003] In order to solve the cracking of PC or PC / ABS materials caused by resistance to disinfectants or chemicals, a crystalline PBT resin is usually introduced into PC. For example, CN115160759 and CN109161179 respectively disclose a method for preparing flame-retardant and chemical-resistant PC / PBT and PC / PBT alloy, by alloying carbonate and polybutylene terephthalate to obtain flame-retardant and chemical-resistant PC / PBT alloy materials. However, the above technology has not been evaluated for the most widely used alcohol disinfectants in medical equipment disinfection. In addition, due to the addition of highly crystalline PBT materials, the shrinkage rate of the material is greatly amplified as the content of PBT resin increases, making the parts molded according to the shrinkage rate materials of PC or PC / ABS in the prior art unusable.
[0004] Therefore, it is of great significance to study a low-shrinkage alcohol-resistant disinfectant PC / PBT alloy material and a preparation method thereof to solve the above problems. Summary of the invention
[0005] The purpose of the present invention is to solve the problems existing in the prior art and to provide a low-shrinkage alcohol-resistant disinfectant PC / PBT alloy material and a preparation method thereof.
[0006] To achieve the above object, the technical solution adopted by the present invention is as follows:
[0007] A low-shrinkage alcohol-resistant disinfectant PC (polycarbonate) / PBT (polybutylene terephthalate) alloy material comprises the following components in parts by weight:
[0008]
[0009]
[0010] The alcohol-resistant agent is octaphenylcyclotetrasiloxane;
[0011] The shrinkage adjusting agent is isopropyl titanate;
[0012] The low-shrinkage alcohol-resistant disinfectant PC / PBT alloy material has a notched impact strength of 468-605 J / m, a longitudinal shrinkage of 0.42-0.51%, a transverse shrinkage of 0.53-0.6%, no cracks are generated in the ethanol solution resistance test, and no cracks are generated or slight cracks are generated in the isopropanol solution resistance test.
[0013] As the preferred technical solution:
[0014] As described above, the low shrinkage alcohol-resistant disinfectant PC / PBT alloy material, the PC resin has a melt index of 15 to 25 g / 10 min under the test conditions of 300°C and 1.2 kg. When the viscosity of the PC resin is lower than 15 g / 10 min, due to the excessive molecular weight of the PC resin, the mobility is weakened, the molecular chains are easily frozen, a large number of voids are easily formed, and the chemical resistance is reduced. When the viscosity of the PC resin is higher than 25 g / 10 min, the mobility of the PC molecular chains is greatly improved, but the molecular chains are too short, causing the material to become brittle.
[0015] As described above, a low shrinkage alcohol-resistant disinfectant PC / PBT alloy material, the intrinsic viscosity of the PBT resin is 1.2-1.3dl / g. When the intrinsic viscosity of polybutylene terephthalate is lower than 1.2dl / g, the crystallization performance of PBT will be improved and the shrinkage rate will be improved. When the viscosity is higher than 1.3dl / g, the fluidity of the material is weakened and it is difficult to complete injection molding.
[0016] In the low shrinkage alcohol-resistant disinfectant PC / PBT alloy material as described above, the toughening agent is MBS (methyl methacrylate, butadiene, styrene terpolymer) resin.
[0017] The present invention also provides a method for preparing a low-shrinkage alcohol-resistant disinfectant PC / PBT alloy material as described in any of the above items, comprising weighing PC resin, PBT resin, toughening agent, alcohol-resistant agent and shrinkage adjuster according to a formula, fully mixing the components in a high-speed mixer, and then extruding and granulating the components in a twin-screw extruder to obtain a low-shrinkage alcohol-resistant disinfectant PC / PBT alloy material.
[0018] As the preferred technical solution:
[0019] In the method for preparing a low-shrinkage alcohol-resistant disinfectant PC / PBT alloy material as described above, the rotation speed of the high-speed mixer is 700 rpm and the mixing time is 8 minutes.
[0020] In the method for preparing the low-shrinkage alcohol-resistant disinfectant PC / PBT alloy material as described above, the rotation speed of the twin-screw extruder is 450-600 rpm, and the processing temperature is 240-260°C.
[0021] Principle of the invention:
[0022] Octaphenylcyclotetrasiloxane is a pharmaceutical intermediate, which is currently mainly used in the field of modification for flame retardancy of PC, and is used as a PC synergistic flame retardant. In the present invention, octaphenylcyclotetrasiloxane is an alcohol-resistant agent, which is stable to heat and chemical reagents, is not easily wetted by polar substances such as water and alcohol, and has outstanding aging resistance, excellent hydrophobicity and electrical insulation. Ethanol and isopropanol are common cost-effective disinfectants that can destroy the peptide bonds of microbial proteins and denature proteins, and can also invade microbial cells to dehydrate proteins and lose activity, etc. However, when alcohol disinfectants are used for disinfection, the strong polarity of alcohols will invade the resin matrix of PC and its alloys, causing PC to crack. Octaphenylcyclotetrasiloxane, with its excellent cyclic structure, is easy to precipitate on the surface of the material, forming a protective film on the surface of the material to prevent the invasion of strong polar alcohol groups. In addition, under the action of hydroxyl groups, the Si-O-Si bonds in the siloxane floating on the surface break and rearrange, directly generating a mixture of polysiloxane and cyclic siloxane, which will further protect the PC resin from damage.
[0023] When the addition amount of octaphenylcyclotetrasiloxane is too high, its high precipitation characteristics can easily cause white precipitates to appear on the surface of the product, affecting the appearance of the product. In addition, it can easily form stress concentration points in the alloy material, resulting in a decrease in the impact properties of the alloy. Therefore, the addition amount should not exceed 1.2 parts.
[0024] Isopropyl titanate is an ester exchange catalyst that can promote ester exchange reactions. The present invention utilizes it to catalyze ester exchange reactions, promote ester exchange between PC and PBT, reduce the crystallization ability of PBT, and thus reduce material shrinkage. The addition of isopropyl titanate promotes ester exchange reactions, but excessive ester exchange reactions will not only lead to a decrease in material performance, but also lead to the generation of a large number of polar groups, which will destroy the protective effect of octaphenylcyclotetrasiloxane on PC / PBT alloys, so the addition amount does not exceed 0.5 parts.
[0025] Octaphenylcyclotetrasiloxane can prevent alcohol disinfectants from corroding the material. Adding octaphenylcyclotetrasiloxane can avoid the large-scale use of PBT and reduce the amount of PBT. The high shrinkage of PC / PBT is mainly caused by the crystallization of PBT itself. The less amount of PBT used reduces the shrinkage of the material, and the ester exchange promotion effect of isopropyl titanate can further reduce the effect of PBT on the shrinkage. Direct use of isopropyl titanate and PBT resin can reduce the shrinkage, but a large amount of PBT resin still needs to be added. Adding a large amount of PBT resin will cause the shrinkage of PC / PBT alloy to be insufficient to reduce to the shrinkage level that meets the PC or PC / ABS mold; and using octaphenylcyclotetrasiloxane alone can prevent alcohol disinfectants from corroding PC / PBT alloy, but after all, it is in the form of surface protection and cannot meet the tolerance to alcohol disinfectants. Therefore, only under the dual effects of isopropyl titanate promoting the ester exchange reaction between PC and PBT to reduce the shrinkage, and at the same time protecting the surface through octaphenylcyclotetrasiloxane, can the above requirements be met.
[0026] Beneficial effects:
[0027] (1) The low shrinkage alcohol-resistant disinfectant PC / PBT alloy material of the present invention has a shrinkage rate of 0.4-0.6%, which is much lower than that of the traditional PC / PBT alloy material. It solves the problem that the PC / PBT material has a large shrinkage rate relative to PC or PC / ABS materials and the mold is not universal. Without changing the mold, it can be applied to PC or PC / ABS low shrinkage molds, and can be used in the field of medical device housings, etc.
[0028] (2) The method for preparing a low shrinkage alcohol-resistant disinfectant PC / PBT alloy material of the present invention utilizes the non-polarity of octaphenylcyclotetrasiloxane to effectively eliminate the erosion of the PC / PBT resin by highly polar disinfectants such as ethanol and isopropanol, thereby reducing the amount of PBT resin required to achieve the same resistance to cracking by disinfectants, thereby reducing the shrinkage rate of the PC / PBT resin;
[0029] (3) The present invention provides a method for preparing a low-shrinkage alcohol-resistant disinfectant PC / PBT alloy material, which selects isopropyl titanate as a shrinkage regulator to promote a partial ester exchange reaction between PC resin and PBT resin, increase the molecular chain length, weaken the resin crystallization performance of PBT, and reduce the shrinkage of the material. DETAILED DESCRIPTION
[0030] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0031] The test methods involved in the embodiments of the present invention and the comparative examples are as follows:
[0032] Notched impact strength: tested in accordance with ASTM D256, notch type A;
[0033] Shrinkage rate: Tested according to ASTM D955, PC / PBT alloy material size: 100mm diameter × 3mm thickness disc;
[0034] Chemical resistance test: tested according to ASTM D543 method, the test strain is 1.0%, the test solvent is 70% ethanol aqueous solution and 70% isopropanol aqueous solution by volume, the brushing interval is 24 hours, and the number of brushing is 10 times.
[0035] Some of the raw material information used in the examples and comparative examples of the present invention are as follows:
[0036] PC resin: Lotte Chemical PC 1070, melt index is 7g / 10min at 300℃ and 1.2kg test conditions;
[0037] PC resin: Lotte Chemical PC 1220, melt index is 21g / 10min at 300℃ and 1.2kg test conditions;
[0038] PBT resin: Yizheng Chemical Fiber GL236, intrinsic viscosity 1.3dl / g;
[0039] PBT resin: Blue Mountain Tunhe TH6100, intrinsic viscosity 1.0dl / g;
[0040] ABS resin: Shanghai Gaoqiao 8391;
[0041] MBS resin: Japan Zhongyuan MBS 722;
[0042] Alcohol-resistant agent: octaphenylcyclotetrasiloxane, purchased from Hubei Xinghengye Technology Co., Ltd.;
[0043] Shrinkage regulator: isopropyl titanate, purchased from Jinan Mingxin Chemical Co., Ltd.
[0044] Example 1
[0045] A method for preparing a low-shrinkage alcohol-resistant disinfectant PC / PBT alloy material, the specific steps are as follows:
[0046] (1) Preparation of raw materials:
[0047] By weight, it includes the following components:
[0048]
[0049]
[0050] (2) PC resin, PBT resin, MBS resin, octaphenylcyclotetrasiloxane and isopropyl titanate were weighed according to the formula, and the components were fully mixed in a high-speed mixer at 700 rpm for 8 minutes, and then extruded and granulated by a twin-screw extruder to obtain a low-shrinkage alcohol-resistant disinfectant PC / PBT alloy material.
[0051] The final low-shrinkage alcohol-resistant disinfectant PC / PBT alloy material has a notched impact strength of 468 J / m, a longitudinal shrinkage of 0.42%, a transverse shrinkage of 0.53%, no cracks in the ethanol solution resistance test, and slight cracks in the isopropanol solution resistance test.
[0052] Example 2
[0053] A method for preparing a low-shrinkage alcohol-resistant disinfectant PC / PBT alloy material, the specific steps are as follows:
[0054] (1) Preparation of raw materials:
[0055] By weight, it includes the following components:
[0056]
[0057] (2) PC resin, PBT resin, MBS resin, octaphenylcyclotetrasiloxane and isopropyl titanate were weighed according to the formula, and the components were fully mixed in a high-speed mixer at 700 rpm for 8 minutes, and then extruded and granulated by a twin-screw extruder to obtain a low-shrinkage alcohol-resistant disinfectant PC / PBT alloy material.
[0058] The final low-shrinkage alcohol-resistant disinfectant PC / PBT alloy material has a notched impact strength of 523 J / m, a longitudinal shrinkage of 0.45%, a transverse shrinkage of 0.56%, no cracks in the ethanol solution resistance test, and slight cracks in the isopropanol solution resistance test.
[0059] Example 3
[0060] A method for preparing a low-shrinkage alcohol-resistant disinfectant PC / PBT alloy material, the specific steps are as follows:
[0061] (1) Preparation of raw materials:
[0062] By weight, it includes the following components:
[0063]
[0064]
[0065] (2) PC resin, PBT resin, MBS resin, octaphenylcyclotetrasiloxane and isopropyl titanate were weighed according to the formula, and the components were fully mixed in a high-speed mixer at 700 rpm for 8 minutes, and then extruded and granulated by a twin-screw extruder to obtain a low-shrinkage alcohol-resistant disinfectant PC / PBT alloy material.
[0066] The final low-shrinkage alcohol-resistant disinfectant PC / PBT alloy material has a notched impact strength of 505 J / m, a longitudinal shrinkage of 0.48%, a transverse shrinkage of 0.58%, no cracks in the ethanol solution resistance test, and slight cracks in the isopropanol solution resistance test.
[0067] Comparative Example 1
[0068] A method for preparing a PC / PBT alloy material is basically the same as in Example 3, except that an equal weight portion of BlueShan Tunhe TH6100 is used to replace the PBT resin in Example 3, that is, the intrinsic viscosity is 1.0 dl / g.
[0069] The final PC / PBT alloy material has a notched impact strength of 503 J / m, a longitudinal shrinkage of 0.56%, a transverse shrinkage of 0.65%, no cracks in the ethanol solution resistance test, and slight cracks in the isopropanol solution resistance test.
[0070] By comparing Example 3 with Comparative Example 1, it can be found that the shrinkage rate of Example 3 is lower than that of Comparative Example 1. This is because the high-viscosity PBT has a longer molecular weight and weaker crystallization properties, which is beneficial to reducing the shrinkage rate of the PC / PBT alloy material.
[0071] Example 4
[0072] A method for preparing a low-shrinkage alcohol-resistant disinfectant PC / PBT alloy material, the specific steps are as follows:
[0073] (1) Preparation of raw materials:
[0074] By weight, it includes the following components:
[0075]
[0076] (2) PC resin, PBT resin, MBS resin, octaphenylcyclotetrasiloxane and isopropyl titanate were weighed according to the formula, and the components were fully mixed in a high-speed mixer at 700 rpm for 8 minutes, and then extruded and granulated by a twin-screw extruder to obtain a low-shrinkage alcohol-resistant disinfectant PC / PBT alloy material.
[0077] The final low-shrinkage alcohol-resistant disinfectant PC / PBT alloy material has a notched impact strength of 574 J / m, a longitudinal shrinkage of 0.48%, a transverse shrinkage of 0.58%, no cracks in the ethanol solution resistance test, and no cracks in the isopropanol solution resistance test.
[0078] Comparative Example 2
[0079] A method for preparing a PC / PBT alloy material is basically the same as that in Example 4, except that an equal amount of Lotte Chemical PC 1070 is used to replace the PC resin in Example 4, that is, the melt index of the PC resin under the test conditions of 300° C. and 1.2 kg is 7 g / 10 min.
[0080] The final PC / PBT alloy material had a notched impact strength of 576 J / m, a longitudinal shrinkage of 0.49%, a transverse shrinkage of 0.57%, cracks in the ethanol solution resistance test, and partial peeling in the isopropanol solution resistance test.
[0081] By comparing Example 4 with Comparative Example 2, it can be found that Example 4 has better tolerance to alcohol disinfectants than Comparative Example 2. This is because the presence of high-viscosity PC leads to a large number of microvoids easily appearing during the shaping process of the PC material, and even the alcohol-resistant agent cannot avoid the invasion of alcohol disinfectants.
[0082] Example 5
[0083] A method for preparing a low-shrinkage alcohol-resistant disinfectant PC / PBT alloy material, the specific steps are as follows:
[0084] (1) Preparation of raw materials:
[0085] By weight, it includes the following components:
[0086]
[0087] (2) PC resin, PBT resin, MBS resin, octaphenylcyclotetrasiloxane and isopropyl titanate were weighed according to the formula, and the components were fully mixed in a high-speed mixer at 700 rpm for 8 minutes, and then extruded and granulated by a twin-screw extruder to obtain a low-shrinkage alcohol-resistant disinfectant PC / PBT alloy material.
[0088] The final low-shrinkage alcohol-resistant disinfectant PC / PBT alloy material has a notched impact strength of 605 J / m, a longitudinal shrinkage of 0.51%, a transverse shrinkage of 0.6%, no cracks in the ethanol solution resistance test, and no cracks in the isopropanol solution resistance test.
[0089] Comparative Example 3
[0090] A method for preparing a PC / PBT alloy material is basically the same as that of Example 5, except that the weight proportion of MBS resin is 3 parts, and isopropyl titanate is not contained.
[0091] The final PC / PBT alloy material has a notched impact strength of 492 J / m, a longitudinal shrinkage of 0.64%, a transverse shrinkage of 0.72%, no cracks in the ethanol solution resistance test, and slight cracks in the isopropanol solution resistance test.
[0092] Comparative Example 4
[0093] A method for preparing a PC / PBT alloy material is basically the same as that of Example 5, except that it does not contain octaphenylcyclotetrasiloxane.
[0094] The final PC / PBT alloy material has a notched impact strength of 515 J / m, a longitudinal shrinkage of 0.47%, a transverse shrinkage of 0.59%, significant cracks in the ethanol solution resistance test, and peeling in the isopropanol solution resistance test.
[0095] By comparing Comparative Example 4 with Example 5, it can be found that in Comparative Example 4, without the addition of the alcohol-resistant agent octaphenylcyclotetrasiloxane, although the shrinkage rate is close to that of PC or PC / ABS materials, and the addition of PBT also improves the alcohol resistance of the alloy, the isopropyl alcohol peeling phenomenon still occurs, which cannot meet the actual use requirements. It is precisely because of the non-polarity of the alcohol-resistant agent that the corrosion of the PC / PBT resin by highly polar disinfectants such as ethanol and isopropyl alcohol can be effectively eliminated, thereby reducing the amount of PBT resin added to achieve the same resistance to disinfectant cracking, thereby reducing the shrinkage rate of the PC / PBT resin.
[0096] Comparative Example 5
[0097] A method for preparing a PC / ABS alloy material is basically the same as that of Example 5, except that an equal weight portion of ABS resin is used to replace the PBT resin, and the weight portion of the MBS resin is 4 parts.
[0098] The final PC / ABS alloy material has a notched impact strength of 535 J / m, a longitudinal shrinkage of 0.43%, a transverse shrinkage of 0.53%, peeling in an ethanol solution resistance test, and fracture in an isopropanol solution resistance test.
[0099] By comparing Example 5 with Comparative Example 5, it can be found that Example 5 has much better tolerance to 70% ethanol aqueous solution and 70% isopropanol aqueous solution than Comparative Example 5. This is because PC and PC / ABS alloys have very poor tolerance to alcohol disinfectants and are very prone to cracking and peeling.
[0100] By comparing Comparative Examples 3, 4 and 5, it can be found that although Comparative Example 3 has an ideal alcohol-resistant disinfectant effect, due to the absence of the shrinkage regulator isopropyl titanate, its lateral and longitudinal shrinkage rates are more than 0.1% higher than those of Comparative Examples 4 and 5, and it does not meet the condition of directly replacing PC or PC / ABS alloy materials without re-molding. The role of the shrinkage regulator is to promote partial ester exchange reaction between PC resin and PBT resin, increase the molecular chain length, weaken the resin crystallization performance of PBT, and reduce the shrinkage of the material.
[0101] Comparative Example 6
[0102] A method for preparing a PC / PBT alloy material is basically the same as that of Example 5, except that the weight proportion of the PBT resin is 40 parts, and octaphenylcyclotetrasiloxane and isopropyl titanate are not contained.
[0103] The final PC / PBT alloy material has a notched impact strength of 604 J / m, a longitudinal shrinkage of 0.75%, a transverse shrinkage of 0.82%, no cracks are generated in the ethanol solution resistance test, and no cracks are generated in the isopropanol solution resistance test.
[0104] By comparing Example 5 with Comparative Example 6, it can be found that the shrinkage rate of Comparative Example 6 is much higher than that of Example 5. If the same alcohol-resistant disinfectant effect is to be achieved, the amount of PBT added is at least 40 parts. As is well known, adding PBT resin to PC can effectively improve the chemical resistance of PC. The high crystallinity of PBT fills the holes of non-crystalline properties and prevents PC from being eroded by alcohol disinfectants. More importantly, the high flexibility of PBT molecular chain segments improves the alcohol-resistant disinfectant properties of PC.
[0105] Comparative Example 7
[0106] A method for preparing a PC / PBT alloy material is basically the same as that of Example 5, except that the weight portion of octaphenylcyclotetrasiloxane is 1.5 parts.
[0107] The final PC / PBT alloy material has a notched impact strength of 450 J / m, a longitudinal shrinkage of 0.53%, a transverse shrinkage of 0.61%, no cracks are produced in the ethanol solution resistance test, no cracks are produced in the isopropanol solution resistance test, and white precipitates are produced on the surface.
[0108] By comparing Example 5 with Comparative Example 7, it can be found that the notched impact performance of Comparative Example 7 decreases and white precipitates appear on the surface. This is because when the addition amount of octaphenylcyclotetrasiloxane is too high, due to the high precipitation characteristics of octaphenylcyclotetrasiloxane, it is very easy to cause white precipitates to appear on the surface of the PC / PBT alloy material, affecting the appearance of the PC / PBT alloy material product. In addition, it is easy to form stress concentration points in the alloy material, resulting in a decrease in the impact performance of the alloy; when the addition amount of octaphenylcyclotetrasiloxane is 1.2 parts, it can achieve excellent alcohol-resistant disinfectant effect.
[0109] Comparative Example 8
[0110] A method for preparing a PC / PBT alloy material is basically the same as that of Example 5, except that the weight portion of isopropyl titanate is 0.6 parts.
[0111] The final PC / PBT alloy material has a notched impact strength of 438 J / m, a longitudinal shrinkage of 0.51%, a transverse shrinkage of 0.59%, tiny cracks in the ethanol solution resistance test, and tiny cracks in the isopropanol solution resistance test.
[0112] By comparing Example 5 with Comparative Example 8, it can be found that tiny cracks appeared during the ethanol and isopropanol tests, and the impact performance dropped to 438 J / m. This is because isopropyl titanate promotes the transesterification reaction, but too much transesterification reaction will not only cause the performance of the material to deteriorate, but also lead to the generation of a large number of polar groups, which will destroy the protective effect of octaphenylcyclotetrasiloxane on the PC / PBT alloy.
Claims
1. A low shrinkage alcohol-resistant disinfectant PC / PBT alloy material, characterized in that The composition comprises the following components in parts by weight: The PC resin has a melt index of 15 to 25 g / 10 min under the test conditions of 300° C. and 1.2 kg; The intrinsic viscosity of the PBT resin is 1.2 to 1.3 dl / g; The alcohol-resistant agent is octaphenylcyclotetrasiloxane; The shrinkage adjusting agent is isopropyl titanate; The low shrinkage alcohol disinfectant-resistant PC / PBT alloy material has a notched impact strength of 468 to 605 J / m, a longitudinal shrinkage of 0.42 to 0.51%, and a transverse shrinkage of 0.53 to 0.6%; The notched impact strength is tested according to ASTM D256, and the notch type is type A; The longitudinal shrinkage and the transverse shrinkage are tested according to ASTM D955.
2. A low shrinkage alcohol-resistant disinfectant PC / PBT alloy material according to claim 1, characterized in that: The toughening agent is MBS resin.
3. A method for preparing a low shrinkage alcohol-resistant disinfectant PC / PBT alloy material as claimed in claim 1 or 2, characterized in that: PC resin, PBT resin, toughening agent, alcohol-resistant agent and shrinkage adjusting agent were weighed according to the formula, and the components were fully mixed by a high-speed mixer, and then extruded into granules by a twin-screw extruder to obtain a low-shrinkage alcohol-resistant disinfectant PC / PBT alloy material.
4. The method for preparing a low shrinkage alcohol-resistant disinfectant PC / PBT alloy material according to claim 3, characterized in that: The rotation speed of the high-speed mixer is 700 rpm, and the mixing time is 8 minutes.
5. The method for preparing a low shrinkage alcohol-resistant disinfectant PC / PBT alloy material according to claim 3, characterized in that: The rotation speed of the twin-screw extruder is 450-600 rpm, and the processing temperature is 240-260°C.
Citation Information
Patent Citations
PBT / PC alloy material and preparation method thereof
CN102382428A
Crosslinked polyester resin molding
JP2003327713A